Production of beauvericin by a strain of Fusarium proliferatum isolated from corn fodder for swine. - Plattner, R D (1994)
Beauvericin, a cyclodepsipeptide, was produced by cultures of three strains of Fusarium proliferatum, M-5991, M-6992, and M-6993, grown on cracked corn. M-5991 produced approximately 1,000-mg/kg levels of fumonisins, moniliformin, and beauvericin.